Urgensi Pengembangan Pembelajaran Kimia Berbasis Kearifan Lokal dan Kepariwisataan untuk Menumbuhkan Literasi Sains Siswa - Khery, Yusran; Rosma Indah, Dahlia; Aini, Miftahul; Asma Nufida, Baiq (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to (1) describe the urgence of developing local wisdom based Chemistry learning and Lombok community tourism in the UNDIKMA Chemistry education study program and (2) describe the learning potential of growing student scientific literacy. This research was conducted in the form of a survey involving 65 students in the UNDIKMA Chemistry education study program. The data were collected using two Likert scale questionnaires. Data were analyzed using the category percentage technique. The results of the study showed that the application of local wisdom based Chemistry learning and tourism in the Lombok community in the UNDIKMA Chemistry education study program still lacked. Student responses to the idea of local wisdom based Chemistry learning and the tourism of the people of Lombok were categorized very well. Students had a high level of confidence that this learning method would increase motivation and attitudes towards learning and provided provisions that were in accordance with the needs of graduates as problem solvers and agents of change in a society that had the uniqueness of local wisdom and tourism potential.